High-Density Lipoprotein Cholosterol May Discriminate Mild and Severe Preeclampsia - Esra Can; Mehmet Mustafa Can; İbrahim Halil Tanboğa; Oluş Api; Murat Biteker; Orhan Ünal (Medical Network, 2011)
OBJECTIVE: Low serum levels of high-density lipoprotein (HDL) cholesterol have been found to be associated with the severity of the inflammatory disorders. Moreover; it has been shown that preeclampsia is a disorder of immune system with predominant involvement of proinflammatory molecules. Therefore the purpose of the present study was to assess whether blood serum HDL cholesterol levels could be used as a predictor of the severity of preeclampsia. STUDY DESIGN: Forty women with preeclampsia were recruited and thirty-five normal pregnant women were matched for both maternal age and gestastional age served as control. The materials were collected immediately after delivery of the fetus, before placenta expulsion and before clumping of the umblical cord in patients and controls whom were in fasting state. Total cholesterol, HDL cholesterol, triglyceride (TG) and low-density lipoprotein (LDL) cholesterol levels were assessed. RESULTS: Among the preeclamptic women, 12 were diagnosed with severe preeclampsia and 28 mild. There were no statistically significant differences between preeclampsia and normal pregnancy except when divided by according to systolic and diastolic blood pressure, proteinuria levels, parity, and HDL cholesterol levels. Of the women with preeclampsia (n=40), 30 % had severe disease. Women with mild and severe preeclampsia had significiantly higher blood pressures at delivery and earlier gestational ages in comparision to control subjects. Although TG, VLDL and LDL levels (p>0.05) were comparable between preeclampsia and normal pregnancies, HDL cholesterol levels were significiantly lower in patients with preeclampsia. Moreover, in subgroup analysis, patients with severe preeclampsia had the lower HDL levels (p<0.05) in comparision with mild preeclampsia. CONCLUSIONS: Blood HDL cholesterol levels measured at delivery were reduced in patients with preeclampsia, and patients with reduced levels of HDL cholesterol had a substantially higher probability of the disease severity in comparision to those with mild preeclampsia or those controls.